Dental discomfort questionnaire as an assessment tool in detecting early childhood caries - Rosli, Muhammad Nasrun Akmal; Abdul Ghani, Murshidah; Supa'at, Salwana; Kharuddin, Azrul Fazwan; Ardini, Yunita Dewi (Ektodermal Displazi Grubu, 2018)
Dental Discomfort Questionnaires (DDQ) is a set of toothache-related-behaviours questions designed by a group of paediatric dentist. This study aims to evaluate the relative dental discomfort among preschool children and to assess awareness of parents for toothache-related-behaviours in their children through DDQ. A cross-sectional study was conducted at IIUM Dental Clinic and Kuantan area involving preschool children 5 years old and below in the period of 10 months from February until November 2016. This research was approved by the IIUM Research Ethic Committee (IREC). Inter-examiner reliability was tested with Kappa statistic (0.83). Participants‟ caries status was assessed using decayed-missing-filled teeth (dmft) and self-administered DDQ is filled out by their parents/caregivers. Data entry and data analysis were done using SPSS and Amos® package version 23 with significance level set at p<0.05. 107 children were examined. Reliability score for behaviour section (DDQ-12) showed a high Cronbach‟s Alpha value of 0.721 while awareness section (DDQ-6) showed a moderate value of 0.326. According to model hypothesis, data showed a good structural equation modelling by goodness of fit between toothache and dmft mediated by behaviours (TLI: 0.674, CFI: 0.754, RMSEA: 0.116). Behaviours concerning putting away sweet things after tasting (21%), bites with molar instead of front teeth (19%) and problems with brushing lower teeth (16%) were frequently reported toothache behaviours by the parents/caregivers. DDQ can act as a reliable tools in helping parents/caregivers and dentist in identifying toothache in young preschool children.